Analisis Tingkat Kepuasan Pelayanan E-Procurement Menggunakan Service Quality Model (Studi di Kabupaten Sidoarjo) - Tri Hasti Wulandari; Yoyon Kusnendar Suprapto; Achmad Affandi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
The development of a region is related to the process of procurement of goods/services. Good and quality service will improve the image of the procurement of goods/services in serving the procurement of goods/services in Sidoarjo Regency. For this reason, measurement of service satisfaction level is needed to determine the quality of services that have been provided so far. The purpose of this study is to determine the distribution of user satisfaction based on five dimensions of service quality,i.e., tangibles, reliability, responsiveness, assurance, empathy with two variables of reality and expectations, and knowing things that hinder the tender process. Retrieval of data is done with two kinds of internal and external questionnaires using simple random sampling method. Overall, 100% of respondents express satisfaction but there are some things that need to be improved. The results of the study from the external side show a very large gap in the completeness aspect of the electronic pre-tender process of 5.60%, while the biggest internal gap is the aspect of tender planning, which is 6.97%. Dimensions that need to be prioritized for improving the quality of service to reduce the gap are assurance dimension from the external and responsiveness from the internal.